Porang flour optimization as a natural tablet binder for bay leaf extract formulation - Nareswari, Tantri Liris; Anandar, Salsabila Fauziah; Putra, Okta Nama; Sarmoko, Sarmoko; Adliani, Nur (Acta Pharmaciae Indonesia, 2024)
Background: The Indonesian pharmaceutical industry relies heavily on imported pharmaceutical raw materials (PRMs), with 90-95% of materials sourced from abroad, leading to increased production costs. Porang tuber (Amorphophallus oncophyllus) contains glucomannan with adhesive properties, making it a potential local alternative for tablet binding agents. Purpose: To optimize bay leaf extract (Syzygium polyanthum) tablet formulation using porang tuber flour and polyvinylpyrrolidone (PVP) as binders through simplex lattice design (SLD). Methods: Porang flour was prepared and characterized for moisture and calcium oxalate content. A tablet formulation optimization study was conducted using Design Expert 13 with porang flour (5-10%) and PVP (0-5%) as independent variables. Responses evaluated included angle of repose, tablet hardness, and disintegration time. The optimized formula was verified and comprehensively characterized. Results: The optimum formula contained 9.86% porang flour and 0.14% PVP, with a desirability value of 0.98. The tablets exhibited satisfactory physical properties: angle of repose 24.70±0.36°, hardness 6.29±0.19 kg, friability 0.51±0.03%, and disintegration time 8.46±0.69 minutes. Statistical analysis confirmed no significant differences between predicted and experimental values (p>0.05). Conclusion: Porang flour can effectively replace synthetic binders in tablet formulations, producing tablets that meet Indonesian Pharmacopoeia standards while reducing dependence on imported excipients.